A política de transparência e acesso à informação pública: uma análise dos portais da transparência em municípios maranhenses- limites e Possibilidades - Silva, Welliton Resende (2022)
This dissertation analyzes the policy of access to public information having as empirical reference the transparency portals in the most populous municipalities of Maranhão. Through the Transparent Brazil Scale (EBT), the CGU assesses the effectiveness of the transparency portals and the Citizen Information Services (SIC) and assigns a grade to Brazilian municipalities. From a methodological point of view, analysis was made of the data released by the CGU and also interviews with public managers and civil society organizations. Regarding the public transparency panorama, EBT revealed that none of the city halls reached the optimal level of transparency. With the level of transparency considered good are the city halls of São Luís, Imperatriz, Açailândia and Buriticupu. With a regular level of transparency are the city halls of Itapecuru-Mirim, Timon, Balsas, ZéDoca, Paço do Lumiar, Bacabal and Tutóia. Barra do Corda, Viana, Grajaú, Coroatá, Barrerinhas, São José de Ribamar, Vargem Grande, Chapadinha and Pinheiro obtainedpoortransparencylevels. And, finally, Santa Luzia, Santa Inês, Codó and Caxias presented a level of transparency considered to be very bad. The survey revealed that 55% of the evaluated municipalities have problems in active and passive transparency. And this problem has to be recognized as a priority and of great relevance by society and the government. Although the portals have become central instruments of public transparency, they have not yet received the attention deserved by most of Maranhão's city halls, failing to comply with the basic determinations indicated by the Law